Systemic effect of radiotherapy before or after nivolumab in lung cancer: an observational, retrospective, multicenter study. Issue 3 (June 2022) - Bassanelli, Maria; Ricciuti, Biagio; Giannarelli, Diana; Cecere, Fabiana Letizia; Roberto, Michela; Giacinti, Silvana; Barucca, Viola; Santarelli, Mario; Ruggeri, Enzo Maria; Marchetti, Paolo; Cognetti, Francesco; Gelibter, Alain; et al.
Background: The combination of radiotherapy (RT) and programmed death 1 inhibitors seems to increase antitumor immune responses. Objective: To assess the outcome and the role of the best combination sequence, i.e. immunotherapy given before, during, and/or after RT, in patients with non-small cell lung cancer (NSCLC). Methods: We conducted an observational, retrospective analysis of 95 consecutive patients with advanced NSCLC who received any radiotherapy treatment and nivolumab, as clinically indicated. Median overall survival (OS) and the 95% confidence interval (CI) were estimated with the Kaplan-Meier method. Cox model was used to obtain hazard ratio (HR) and associated 95% CI with statistical inference by log-rank statistic. Results: Median OS was 11.9 months (95% CI, 6.6–17.2). Patients who received radiotherapy during an immune checkpoint inhibitor treatment started more than 60 days before showed a better outcome than patients who started immunotherapy over 60 days after RT ending (HR, 2.90 [1.37–6.12], p = 0.005; median OS, 22.4 months vs 8.6 months, p = 0.005). Median progression-free survival was 6.3 months (95% CI, 4.6–8.0). Conclusions: This study shows that combining irradiation with nivolumab for the treatment of advanced NSCLC leads to improved OS. The optimal time window for the combination of RT and immunotherapy seems to play a critical role for therapeutic antitumor response derived by abscopal effect.